THE CORRELATION BETWEEN THE HABIT OF CARRYING OUT JAMAAH PRAYERS WITH THE DISCIPLINE ATTITUDE OF STUDENTS - Anne Andriane; Erhamwilda Erhamwilda (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
AbstractSalat is an obligation for every Muslim. Prayer in congregation is rewarded by Allah Almighty twenty seven times higher than prayer alone. With regular prayer in congregation one will get used to the discipline of managing time. This study aims to determine whether there is a correlation between the habits of students praying in congregation with the attitude of student discipline. The study was conducted with a quantitative approach, descriptive method, and the type of correlation research. This research was conducted on eighth grade students in one Islamic junior high school in the city of Bandung. The study population was 8th grade students totaling 294 students. Samples were taken with a random sampling technique of 114 students. Hypothesis testing is done by 5% error significance. Data collection research instruments include: Likert scale, questionnaires, documentation, interviews, and observations. Presentation of data uses frequency distribution, unit analysis, statistics, normality test, validity test, reliability test, correlation, and hypothesis test summary. The results of this study indicate that there is a significant positive correlation between the habit of carrying out congregational prayers with the discipline of students. It was concluded that to improve student discipline could be done by praying in congregation.Keywords: Habits, jamaah prayer, attitude of discipline Abstrak Shalat merupakan kewajiban bagi setiap Muslim. Sholat berjamaah diberi ganjaran pahala oleh Allah Swt dua puluh tujuh kali lebih tinggi dari sholat sendirian. Dengan rutin sholat berjamaah seorang akan terbiasa dengan disiplin mengatur waktu. Penelitian ini bertujuan untuk mengetahui apakah terdapat korelasi antara kebiasaan siswa sholat berjamaah dengan sikap disiplin siwa. Penelitian dilakukan dengan pendekatan kuantitatif, metoda deskriptif, dan jenis penelitiannya korelasi. Penelitian ini dilakukan pada siswa kelas VIII di salah satu SMP Islam di Kota Bandung. Populasi penelitian adalah siswa kelas 8 yang berjumlah 294 siswa, Sampel diambil dengan teknik random sampling sebanyak 114 siswa. Uji hipotesis dilakukan dengan signifikasi kesalahan 5%. Instrumen penelitian pengumpul data meliputi: skala likert, angket, dokumentasi, wawancara, dan observasi. Penyajian data menggunakan distribusi frekuensi, analisis unit, statistik, uji normalitas, uji validitas, uji reliabilitas, korelasi, dan ringkasan uji hipotesis. Hasil penelitian ini menunjukkan terdapat hubungan korelasi positif yang signifikan antara kebiasaan melaksanakan shalat berjamaah dengan sikap disiplin siswa. Disimpulkan untuk meningkatkan disiplin siswa dapat dilakukan dengan pembiasaan sholat berjamaah.Kata Kunci: Kebiasaan, Shalat Berjamaah, Sikap Disiplin.